2013
DOI: 10.4236/jbbs.2013.32018
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Antinociceptive Effects Induced by Gravity Stress in Rats

Abstract: A number of studies have demonstrated that sex differentially affects responses to stress and pain. In this study, sex-related differences in pain responding were investigated in a gravity-induced analgesia model, where the effects of stressful high-gravity loading (1.5G or 2.0G for 10 min) on nociceptive behavior in male and female rats were investigated. In each rat, eight sites (nose, both forepaws, upper and lower back, both hind paws and tail) were selected to apply noxious stimuli using a von Frey-type n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Other studies have also shown the influence of gender and estrogen on pain-related changes during stress exposure. Stress-induced analgesia is more profound in males than in females suggesting that males are more sensitive to stress than females (Kimoto et al, 2013). It has been reported that kappa opioid receptor-mediated anti-nociceptive and anti-hyperalgesic effects are enhanced by exogenous or endogenous estrogen in the females rats (Lawson et al, 2010).…”
Section: Influence Of Gender On Stress Modulatory Role Of Opioidsmentioning
confidence: 99%
“…Other studies have also shown the influence of gender and estrogen on pain-related changes during stress exposure. Stress-induced analgesia is more profound in males than in females suggesting that males are more sensitive to stress than females (Kimoto et al, 2013). It has been reported that kappa opioid receptor-mediated anti-nociceptive and anti-hyperalgesic effects are enhanced by exogenous or endogenous estrogen in the females rats (Lawson et al, 2010).…”
Section: Influence Of Gender On Stress Modulatory Role Of Opioidsmentioning
confidence: 99%